Shaping of object representations in the human medial temporal lobe based on temporal regularities - Schapiro, Anna C. (2012)
Regularities are gradually represented in cortex after extensive experience [1], and yet they can influence behavior after minimal exposure [2,3]. What kind of representations support such rapid statistical learning? The medial temporal lobe (MTL) can represent information from even a single experience [4], making it a good candidate system for assisting in initial learning about regularities. We combined anatomical segmentation of the MTL, high-resolution functional magnetic resonance imaging (fMRI), and multivariate pattern analysis (MVPA) to identify representations of objects in cortical and hippocampal areas of human MTL, assessing how these representations were shaped by exposure to regularities. Subjects viewed a continuous visual stream containing hidden temporal relationships—pairs of objects that reliably appeared nearby in time. We compared the pattern of blood oxygen level-dependent (BOLD) activity evoked by each object before and after this exposure, and found that perirhinal cortex (PRC), parahippocampal cortex (PHC), subiculum, CA1, and CA2/CA3/dentate gyrus (CA2/3/DG) encoded regularities by increasing the representational similarity of their constituent objects. Most regions exhibited bidirectional associative shaping, while CA2/3/DG represented regularities in a forward-looking predictive manner. These findings suggest that object representations in MTL come to mirror the temporal structure of the environment, supporting rapid and incidental statistical learning.